Associations of metabolic status with all-cause mortality among individuals with osteoarthritis: A prospective cohort study - Hao Yang; Muhui Zeng; Tianxiang Fan; Haowei Chen; Xiaofeng Fang; Zhong Alan Li; Xiaoshuai Wang; David J. Hunter; Changhai Ding; Zhaohua Zhu (Journal of Orthopaedic Translation)
Background: Individuals with osteoarthritis (OA) often experience significant changes in their metabolic status and have a higher risk of mortality compared to the general population. However, no study has quantified the metabolic status of OA patients. Moreover, the association between metabolic status and risk of mortality among OA patients remains unclear. Methods: The analysis included baseline populations with OA from the UK Biobank (UKBB) study and the National Health and Nutrition Examination Survey (NHANES) 1999–2018. Metabolic status was assessed using composite scores based on body mass index, waist-hip ratio, blood pressure, fasting plasma glucose, hemoglobin A1c, C-reactive protein, triacylglycerols, and lipoproteins. Restricted cubic splines were used to define healthy ranges for each indicator regarding mortality risk. Factors received 1 if within a healthy range, else 0. Total scores ranged from 0 to 7, with 3+ indicating good metabolic health. The traditional metabolic syndrome criteria (ATP III) and the Strict definition were used for comparison. Associations between metabolic unhealth and mortality were examined using Cox proportional hazards models. Integrated Discrimination Improvement (IDI) evaluated discriminatory capacity, and Net Reclassification Improvement (NRI) assessed reclassification performance in predicting ten-year mortality. Results: Among 44,302 UKBB OA participants, 36.0 % were metabolically unhealthy (scores: 0–2), while in 5233 NHANES OA participants, 39.1 % were metabolically unhealthy based on our newly-established definition. After adjustment for covariates, metabolically unhealthy individuals had significantly higher all-cause mortality risk (HR: 1.36; 95 % CI: 1.26–1.47 in UKBB; HR: 1.16; 95 % CI: 1.03–1.30 in NHANES) compared to metabolically healthy individuals. In UKBB, compared to ATP III definition, the changes in IDI and NRI for our newly-established definition were 0.10 % (0.01 %, 0.20 %) and 10.60 % (1.8 %, 13.60 %), respectively. When the comparison was made with the Strict definition, the newly-established definition showed changes in IDI and NRI of 0.18 % (0.10 %, 0.20 %) and 12.10 % (10.30 %, 13.80 %), respectively. results. Conclusions: A new definition for quantifying metabolic unhealth in OA was proposed. It identified a significant mortality risk with poorer metabolic status and outperformed general definitions in predictive accuracy. conclusion. The translational potential of this article: OA is the leading joint disease worldwide, carrying a heavy health burden. Our newly established definition, evaluating metabolic health through waist-to-hip ratio, BMI, blood pressure, glucose, lipids, and C-reactive protein, identified 36.0 % OA patients in UK Biobank and 39.1 % OA patients in NHANES as having poor metabolic status, which is applicable in clinical and research settings. This study also showed that poor metabolic status, as classified by these criteria, is significantly correlated with an elevated risk of all-cause mortality in OA patients. It further highlights the importance of maintaining a holistic approach to care for OA patients, emphasizing the need to address both joint and metabolic health.